Supramolecular Arrangement in Styphnic Acid and Naphthalene-1, 4-diol (1 : 1) through a Novel Synthetic Rote for Styphnic Acid. (18th August 2013) - Refat, Moamen S.; Saad, Hossam A.; El-Sayed, Mohamed Y.; Adam, Abdel Majid A.; Yeşilel, Okan Zafer; Taş, Murat
Abstract : The chemical preparation and crystal structure of styphnic acid and naphthalene-1, 4-diol (1 : 1) (I) have been reported. The compound crystallizes in the orthorhombic system in space group Pnma and cell parameters a = 6.6712 ( 2 ), b = 16.8267 ( 7 ), c = 13.6450 ( 5 )  Å and V = 1531.71 ( 10 )  Å 3, and Z = 4 . Crystal structure has been determined and refined to R = 0.0576 . The crystal structure of I, the asymmetric unit, contains C6 H2 N3 O7, C10 H7 O, and it is a half portion of both styphnic acid and naphthalene-1, 4-diol. The O1–H1⋯ O2 intramolecular hydrogen bond was found between the O–H and a nitro group in the styphnic acid unit.